Some new species and new record of the genus Arboridia Zachvatkin (Hemiptera: Cicadellidae: Typhlocybinae) from six provinces of China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2013)
In the present paper, nine new species, Arboridia anteoculara, A. baiyunensis, A. reniformis, A. lunula, A. cuihuashana, A. paraprocessa, A. echinata, A. tridentata, A. zhenyuana spp. n. and a new record, A. agrillacea from China, are de-scribed and illustrated and a key for identification of Chinese species is provided.